Examining the environmental risk factors of progressive-onset and relapsing-onset multiple sclerosis: recruitment challenges, potential bias, and statistical strategies - Li, Ying; Saul, Alice; Taylor, Bruce; Ponsonby, Anne-Louise; Simpson-Yap, Steve; Blizzard, Leigh; Broadley, Simon; Lechner-Scott, Jeannette; Ausimmune/AusLong Investigators Group; Karabudak, Rana; Patti, Francesco; Eichau, Sara; et al. (Journal of neurology, 2024)
It is unknown whether the currently known risk factors of multiple sclerosis reflect the etiology of progressive-onset multiple sclerosis (POMS) as observational studies rarely included analysis by type of onset. We designed a case-control study to examine associations between environmental factors and POMS and compared effect sizes to relapse-onset MS (ROMS), which will offer insights into the etiology of POMS and potentially contribute to prevention and intervention practice. This study utilizes data from the Primary Progressive Multiple Sclerosis (PPMS) Study and the Australian Multi-center Study of Environment and Immune Function (the AusImmune Study). This report outlines the conduct of the PPMS Study, whether the POMS sample is representative, and the planned analysis methods. The study includes 155 POMS, 204 ROMS, and 558 controls. The distributions of the POMS were largely similar to Australian POMS patients in the MSBase Study, with 54.8% female, 85.8% POMS born before 1970, mean age of onset of 41.44 ± 8.38 years old, and 67.1% living between 28.9 and 39.4° S. The POMS were representative of the Australian POMS population. There are some differences between POMS and ROMS/controls (mean age at interview: POMS 55 years vs. controls 40 years; sex: POMS 53% female vs. controls 78% female; location of residence: 14.3% of POMS at a latitude ≤ 28.9°S vs. 32.8% in controls), which will be taken into account in the analysis. We discuss the methodological issues considered in the study design, including prevalence-incidence bias, cohort effects, interview bias and recall bias, and present strategies to account for it. Associations between exposures of interest and POMS/ROMS will be presented in subsequent publications.
Keywords: recidiva; Humans; Case-Control Studies; chronicko-progresivní roztroušená skleróza; lidé středního věku; Multiple Sclerosis; multicentrické studie jako téma; studie případů a kontrol; Multiple Sclerosis, Chronic Progressive; Female; rizikové faktory; dospělí; lidé; Adult; ženské pohlaví; roztroušená skleróza; Male; Middle Aged; Case–control; Progressive-onset multiple sclerosis; Subject recruitment; Recurrence; Environmental factors; Bias; věk při počátku nemoci; mužské pohlaví; Age of Onset; Austrálie; Multicenter Studies as Topic; Australia; Risk Factors